NÍVEIS CRÍTICOS DE BORO PARA A CULTURA DO GIRASSOL EM SOLOS COM TEXTURAS CONTRASTANTES - MANOEL EUBA NETO (Revista Caatinga, 2014)
Boron deficiency in sunflower cultivation can cause decreased production, mainly by the fall of the inflorescence diameter. Most soils, especially in the tropics present low content of boron (B) available. To ascertain the response of sunflower to boron application in different orders of tropical soils with different tex- tures, we carried out an experiment under controlled condition. Were applied to the soil samples collected in the layer 0-20 cm, four doses of B as boric acid (H3BO3) in solutions at concentrations of 0.0; 0.04; 0.08 and 0.16 mol m-3. The soils were: PAC - Argissolo Acinzentado; PVe - Argissolo Vermelho eutrófico; PVA - Argissolo Vermelho-Amarelo; RL - Neossolo Litólico; RY - Neossolo Flúvico; VX - Vertissolo Háplico. The experimental design used was a randomized blocks in factorial scheme 4 x 6 (doses x soils) with four replica- tions and one plant per pot. Quantification of B content was performed by extraction method with barium chlo- ride solution of 5.0 mol m-3 subjected to heating with microwave radiation and determining the B content in the soil was performed by colorimetric technique using the azomethine-H reagent. The contents at levels sufficient to allow the soil B established independent of the dose added, a yield exceeding 90% yield on. The highest dry matter yield of sunflower was associated with the B concentration in the soil between 0.04 and 0.08 mol m-3 and there was a decrease with higher concentrations.